Molecular mechanisms of thermal resistance of the insect trypanosomatid Crithidia thermophila - Aygul Ishemgulova; Anzhelika Butenko; Lucie Kortišová; Carolina Boucinha; Anastasiia Grybchuk‐Ieremenko; Karina Alessandra Morelli; Martina Tesařová; Natalya Kraeva; Danyil Grybchuk; Tomáš Pánek; Pavel Flegontov; Julius Lukeš; et al. (2017)
In the present work, we investigated molecular mechanisms governing thermal resistance of a monoxenous trypanosomatid Crithidia luciliae thermophila, which we reclassified as a separate species C. thermophila. We analyzed morphology, growth kinetics, and transcriptomic profiles of flagellates cultivated at low (23°C) and elevated (34°C) temperature. When maintained at high temperature, they grew significantly faster, became shorter, with genes involved in sugar metabolism and mitochondrial stress protection significantly upregulated. Comparison with another thermoresistant monoxenous trypanosomatid, Leptomonas seymouri, revealed dramatic differences in transcription profiles of the two species with only few genes showing the same expression pattern. This disparity illustrates differences in the biology of these two parasites and distinct mechanisms of their thermotolerance, a prerequisite for living in warm-blooded vertebrates.